2023
DOI: 10.3390/ijms242115677
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling the Intricate Roles of Exosomes in Cardiovascular Diseases: A Comprehensive Review of Physiological Significance and Pathological Implications

Shuai Zhang,
Yu Yang,
Xinchen Lv
et al.

Abstract: Exosomes, as potent intercellular communication tools, have garnered significant attention due to their unique cargo-carrying capabilities, which enable them to influence diverse physiological and pathological functions. Extensive research has illuminated the biogenesis, secretion, and functions of exosomes. These vesicles are secreted by cells in different states, exerting either protective or harmful biological functions. Emerging evidence highlights their role in cardiovascular disease (CVD) by mediating co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 237 publications
(272 reference statements)
1
1
0
Order By: Relevance
“…Although we observed similar results in ECs under all EXO treatments, our data demonstrate an enhanced protective effect of LAMA2-EXOs in cardiomyocytes, mainly after 1.5 h of reoxygenation compared to untreated cells; LAMA2-EXO treatment resulted in cells reaching baseline values more quickly than those treated with gel-EXOs. EXOs have anti-apoptotic characteristics, and this protection has been previously studied [49]. Similar to our findings, a recent study demonstrated a protective effect of EXOs, with a 60% decrease in apoptosis in cardiomyocytes under ischemia-reperfusion injury [50].…”
Section: Discussionsupporting
confidence: 91%
“…Although we observed similar results in ECs under all EXO treatments, our data demonstrate an enhanced protective effect of LAMA2-EXOs in cardiomyocytes, mainly after 1.5 h of reoxygenation compared to untreated cells; LAMA2-EXO treatment resulted in cells reaching baseline values more quickly than those treated with gel-EXOs. EXOs have anti-apoptotic characteristics, and this protection has been previously studied [49]. Similar to our findings, a recent study demonstrated a protective effect of EXOs, with a 60% decrease in apoptosis in cardiomyocytes under ischemia-reperfusion injury [50].…”
Section: Discussionsupporting
confidence: 91%
“…The observed stem-cell-mediated benefits have been shown to be attributable to the paracrine functions of stem cells. In this aspect, exosomes appear to play a key role, particularly because of their contents of microRNAs, which have been found to be of great clinical potential in the treatment of ischemic heart disease [118,144,[191][192][193]. Taking into account the limited availability of autologous stem cells, exosomes from their allogeneic and xenogeneic counterparts may also offer significant therapeutic advantages [104].…”
Section: Discussionmentioning
confidence: 99%